The abolition of surgery and sex change and birth registration (BioLaw Journal - Rivista di BioDiritto, 2024)
The author in the first part of essay analysis the problem of the abolition of surgery and sex change: a change realized with the decret-loi n. 150/ 2011 and the jurisprudence of 2015 and 2023. In the second part analysis the possibility in the ambit of birth registration to change the rule binary (M-F) in a rule trinary (M-F-X) or to abandon the official registration of sex.
Keywords: Abolition of surgery; birth registration; sex change; rule binary; rule trinery